KAJIAN AYAT PERNIKAHAN PERSPEKTIF WAHBAH ZUHAILI DALAM TAFSIR AL-MUNIR - M. Khoirul Muzakki; Indira Resty Fridiana (Prodi Hukum Keluarga Islam IAI Uluwiyah Mojokerto, 2024)
The family is the smallest group in society, consisting of husband, wife, and children. This is the principle of the formation of society. Most people think that the factors of peace in family life are material, but many wealthy people lack peace at home, resulting in frequent quarrels and discomfort. Problems that arise in the household can threaten the longevity of a marriage and even lead to divorce. This occurs because each partner's expectations are not met and because of a lack of mental, social, and spiritual preparation. Next, the researcher examines the verses on marriage in Wahbah Zuhayli's Tafsir al-Munir as a solution for creating a peaceful family today. The hope is to find relevant interpretations and even solutions to address current problems. For the author, this is useful for increasing insight into mindsets, attitudes, and experiences as an effort to improve the quality of learning, by understanding the characteristics of sakinah, mawaddah, and rahmah in the family. The research problem formulation in this study is (1) What is the Qur'an's view of a peaceful family? (2) How are the verses about the sakinah, mawaddah, wa rahmah family interpreted in Wahbah Zuhayli's commentary on al-Munir? This research is a library research that uses al-Munir's interpretation as the main source of research. This research uses a descriptive-analytic approach. The method used is descriptive analysis, namely explaining the interpretation to find out the results of the interpretation and differences in the field of interpretation. Another analysis using the maudhu'i method is to discuss verses according to appropriate themes by collecting and studying in depth various aspects related to asbab al-nuzul, mufradat and interpretation of these verses.